Current trends in the production and application of titanium alloys - Leokha , F.L.; Khrychikov , V.E. (Theory and Practice of Metallurgy, 2025)
Purpose: Analysis of the state of scientific research in the field of production and application of titanium alloys and trends in their development over the past 20 years. Methodology: Narrative review and analysis of the literature with the most current publications in open sources Google Scholar, Sciencedirect, Researchgate, Scopus. Results: Titanium is distinguished by its strength, low density, corrosion resistance, biocompatibility and heat resistance, which makes it important for industry. More than 100 titanium alloys have been created, of which only 20–30 have reached commercial status. The most common is Ti-6Al-4V (over 50% of applications), another 20–30% are pure titanium alloys. They are used in the aerospace, medical, automotive and chemical sectors. Titanium metallurgy is based on vacuum arc and electron beam remelting, but an active search for alternative technologies continues, such as electroslag remelting of titanium alloys. Additive technologies are also being actively introduced. The scientific novelty lies in the comprehensive generalization of modern research related to the production and application of titanium alloys with an emphasis on modern methods of remelting titanium charge into a finished product. The publication includes the most relevant sources that are not yet available in other reviews. Practical significance. The publication will help scientists, engineers, teachers, and students to quickly navigate the array of existing knowledge, avoid duplication of research, and better plan further activities.